Assessing biosolids quality at the Mu'ta-Mazar wastewater treatment plant for the years 2016–2019. (30th January 2023) - AL-Hmoud, Nisreen; Alrwashdeh, Mumen; Hayek, Bassam
Abstract: Disposal of sludge produced by sewage treatment plants is an increasing problem worldwide. Recycling of treated wastewater sludge as biosolids is a beneficial and environmentally sustainable management option. Deutsche Gesellschaft fuer Internationale Zusammenarbeit (GIZ) GmbH through its German-Jordanian Programme 'Management of Water Resources, and in collaboration with Royal Scientific Society of Jordan has launched a project to pilot decentralized management of sludge. Through this project, the quality of sludge generated from Mu'ta-Mazar Wastewater Treatment Plant (WWTP), which has been selected as the pilot area for Decentralized Integrated Sludge Management (DISM) project, has been assessed over four consecutive years (2016–2019). A complete assessment of the sludge qualities in terms of physical, chemical, pharmaceutical and microbial parameters was conducted. The results of this study will help in evaluating the feasibility of co-digestion of sludge by processing sludge with the other sources of organic waste. The aim of this study is to contribute towards environmental protection and the use of renewable energies and to increase energy efficiency through production of bioenergy and recovery of nutrient content of wastewater sludge and food waste. The study also demonstrates financially viable and technically feasible solutions for the current sludge management issues in WWTPs in Jordan. HIGHLIGHTS: Potential use of sludge generated from Mu'ta WWTP of Jordan in land application. Assessment of the sludge quality in terms of microbiological and metal contents is critical for safe use on the environment and human health. Biosolids generated from the Mu'ta WWTP contain valuable nutrients such as nitrogen (N), phosphorus (P), and carbon (energy), and its recycling would be economically feasible. Emerging pollutants are important parameters to be monitored periodically in different types of sludge. Graphical Abstract